Music in crime, resistance, and identity - Peters, Eleanor (Eleanor J.) (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book considers the intersection of music, politics and identity, focusing on music (genres) across the world as a form of political expression and protest, positive identity formations, but also how the criminalisation, censuring, policing and prosecution of musicians and fans can occur. All-encompassing in this book is analyses of the unique contribution of music to various aspects of human activity through an international, multi-disciplinary approach. The book will serve as a starting point for scholars in those areas where there has been an uncertain approach to this subject, while those from disciplines with a more established canon of music analysis will be informed about what each perspective can offer. The approach is international and multi-disciplinary, with the contributing authors focusing on a range of countries and the differing social and cultural impact of music for both musicians and fans. Academic disciplines can provide some explanations, but the importance of the contribution of practitioners is vital for a fully rounded understanding of the impact of music. Therefore, this book takes the reader on a journey, beginning with theoretical and philosophical perspectives on music and society, proceeding to an analysis of laws and policies, and concluding with the use of music by educational practitioners and the people with whom they work. This book will appeal to students and scholars in subjects such as sociology, criminology, cultural studies, and across the wider social sciences. It will also be of interest to practitioners in youth justice or those with other involvement in the criminal justice system"--
Introduction / Eleanor Peters -- Four Dead in Ohio : Revolutionary Music and American Protests / Andrew R. Wilczak -- The Norwegian Black Metal Second Wave : A Space for Performative Politics / Kevin Hoffin -- Musical experience as Penumbra, Haecceity & Utopian Fractal Musica Penumbra / Craig Hammond -- Policing Death : Indonesian Death Metal music and alleged or apparent criminality / Kieran James -- Decriminalising Rap Beat by Beat : Two Questions in Search of Answers / Lambros Fatsis -- Music : Human rights and harms / Eleanor Peters -- Music in the Collective Lives of Prisoners / Chris Waller -- The benefits of music engagement projects on young people : A music and education perspective / Justin Boreland and Eleanor Peters.
Keywords: Music and crime; Music -- Political aspects; Identity (Philosophical concept); MUSIC / General; SOCIAL SCIENCE / Sociology / General